Carbon nanotube reinforced material and preparation method thereof, composite material and preparation method thereof

By loading corrosion inhibitors in the inner cavity of carbon nanotubes and keeping the outer wall clean, the problem of the contradiction between strength and corrosion resistance of metal materials in extreme environments is solved, and high strength and high corrosion resistance are achieved.

CN118345367BActive Publication Date: 2024-12-13INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310059775.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2024-12-13
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

It is difficult for existing metal materials to take into account high strength and high corrosion resistance in extreme environments, especially in corrosive media, corrosion is prone to accelerated by microcouple effects.

Method used

By loading corrosion inhibitors in the tubes of carbon nanotubes and keeping the outer wall clean, the internal cavity load corrosion inhibitors and external wall strengthening functions of carbon nanotubes are used to form a dual function of "inner cavity corrosion inhibition and outer wall strengthening".

Benefits of technology

Carbon nanotube reinforced materials that take into account both high strength and high corrosion resistance in extreme environments are realized, which suppresses corrosion by releasing corrosion inhibitors through the inner cavity and increases strength through the outer wall.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118345367B_ABST
    Figure CN118345367B_ABST
Patent Text Reader

Abstract

The present application provides a carbon nanotube reinforced material and a preparation method thereof, a composite material and a preparation method thereof, comprising carbon nanotubes; a corrosion inhibitor is loaded in the carbon nanotube body; and the outer wall of the carbon nanotube is a clean wall surface. The carbon nanotube reinforced material and a preparation method thereof, a composite material and a preparation method thereof can take into account both high strength and high corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and specifically to a carbon nanotube reinforced material and a preparation method thereof, a composite material and a preparation method thereof. Background Art

[0002] my country's military, marine, energy, equipment manufacturing and other fields are constantly expanding to extreme environments such as the deep sea and polar regions. These complex and harsh environments can easily cause structural mechanical instability and corrosion failure of equipment, seriously affecting the service safety and life of the equipment. Therefore, the new extreme service environment requires the structural materials of the equipment to have higher strength and higher corrosion resistance. At present, the development of metal structural materials is mainly aimed at achieving strengthening and toughening. By regulating heterogeneous structures such as in-situ precipitation phases, external reinforcement phases, and micro-nano gradient structures, fruitful results have been achieved in the strengthening and toughening of metal materials. A variety of high-strength and high-toughness metals and their composite materials are constantly emerging.

[0003] However, in corrosive media, heterogeneous structures such as precipitated phases and reinforcement phases often have intrinsic corrosion potential differences with the base metal, which can easily produce micro-galvanic effects and accelerate corrosion. This has led to the poor corrosion resistance of most high-strength metals and their composite materials. In order to solve this problem, researchers have improved the corrosion resistance of high-strength metals and their composite materials to a certain extent by regulating the composition and morphology of precipitated phases, optimizing phase interfaces, and improving the composition and structure of surface films, but most of these measures are at the expense of high strength. It can be seen that the metal materials in the prior art cannot take into account both high strength and high corrosion resistance.

[0004] Therefore, how to provide a carbon nanotube reinforced material and a preparation method thereof, a composite material and a preparation method thereof that can achieve both high strength and high corrosion resistance has become an urgent problem that technicians in this field need to solve. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present application is to provide a carbon nanotube reinforced material and a preparation method thereof, a composite material and a preparation method thereof, which can take into account both high strength and high corrosion resistance.

[0006] In order to solve the above problems, the present application provides a carbon nanotube reinforced material, comprising carbon nanotubes; a corrosion inhibitor is loaded in the carbon nanotube body; and the outer wall of the carbon nanotube is a clean wall surface.

[0007] Preferably, the corrosion inhibitor comprises an inorganic corrosion inhibitor;

[0008] and / or, the melting point of the corrosion inhibitor is higher than 680°C;

[0009] Preferably, the inorganic corrosion inhibitor includes at least one of molybdate, tungstate, vanadate, etc.;

[0010] and / or, the carbon nanotubes include single-walled carbon nanotubes or multi-walled carbon nanotubes;

[0011] And / or, the diameter of the carbon nanotube is less than 50 nm; the length of the carbon nanotube is less than 50 μm;

[0012] And / or, the mass of the corrosion inhibitor loaded in the carbon nanotube body is greater than 3 times the mass of the carbon nanotube body.

[0013] According to another aspect of the present application, there is provided a method for preparing the above-mentioned carbon nanotube reinforced material, comprising the following steps:

[0014] Step (1): loading a corrosion inhibitor into the carbon nanotube to obtain a nano-reinforced tube;

[0015] Step (2): Cleaning the nano-reinforced tubes to form a clean wall surface on the outer wall of the carbon nanotubes; obtaining a carbon nanotube reinforced material.

[0016] Preferably, in step (1), loading the carbon nanotube with a corrosion inhibitor comprises the following steps:

[0017] The purified carbon nanotubes and the corrosion inhibitor are mixed evenly in water to form a mixed solution; the mixed solution is subjected to a boiling treatment to make the mixed solution boil, so that the corrosion inhibitor is loaded in the tube body of the purified carbon nanotubes;

[0018] Preferably, in the mixed solution, the mass ratio of the corrosion inhibitor to the purified carbon nanotubes is greater than 4:1;

[0019] Preferably, the purified carbon nanotubes and the corrosion inhibitor are uniformly mixed in water to form a mixed solution, which comprises the following steps: after the purified carbon nanotubes and the corrosion inhibitor are mixed in water, the solution is stirred under a constant temperature environment;

[0020] Preferably, the temperature of the constant temperature environment is 30-50° C.; preferably, the constant temperature environment is controlled by an oil bath; preferably, the stirring comprises the following steps: using magnetic stirring, and controlling the rotation speed to be greater than 800 rpm.

[0021] Preferably, the method for preparing purified carbon nanotubes comprises the following steps: adding carbon nanotubes to a mixed solution of HNO3:H2SO4=1:2-4 and subjecting it to ultrasonic oscillation, followed by carbon nanotube filtration, carbon nanotube washing and carbon nanotube drying to obtain purified carbon nanotubes;

[0022] Preferably, the ultrasonic oscillation time is 1 to 6 hours;

[0023] Preferably, during the ultrasonic oscillation process, a constant temperature environment is used. Preferably, the temperature of the constant temperature environment is 30 to 60° C. Preferably, the constant temperature environment is controlled by a water bath;

[0024] Preferably, the carbon nanotubes are cleaned by repeatedly washing with deionized water until the filtrate is neutral;

[0025] Preferably, the temperature for drying the carbon nanotubes is 40 to 80° C., and the time for drying the carbon nanotubes is 1 to 3 hours.

[0026] Preferably, the boiling treatment comprises the following steps: Step S1: evacuating the container where the mixed solution is located to make the mixed solution boil; Preferably, evacuating the container where the mixed solution is located comprises the following steps: evacuating the container with a vacuum pump to a pressure lower than -0.0950 MPa;

[0027] Preferably, after evacuating the container containing the mixed solution, the following steps are further included:

[0028] Step S2: performing pressure relief treatment on the container where the mixed solution is located; preferably, in step S2, performing pressure relief treatment on the container where the mixed solution is located comprises: releasing the pressure until the air pressure in the container is equal to the atmospheric pressure;

[0029] Step S3: repeat step S1-step S2;

[0030] Preferably, in step S3, the number of repetitions is 3 to 30 times;

[0031] Preferably, in the last repetition process, the vacuum is maintained for 0 to 120 minutes before the pressure relief treatment is performed.

[0032] Preferably, after step (1) and before step (2), the following steps are further included:

[0033] Filtering the mixed solution after the treatment in step S3 to obtain a nano-enhanced tube filter residue;

[0034] Preferably, filtering the mixed solution after the treatment in step S3 comprises the following steps: filtering the mixed solution with filter paper or filter membrane to obtain nano-slowly enhanced filter residue, wherein the filter residue includes nano-enhanced tubes;

[0035] Preferably, in step (2), cleaning the nano-enhanced tubes comprises the following steps:

[0036] The nano-enhanced tubes are cleaned with a mixed solution of alcohol and water; preferably, the water is deionized water; preferably, the volume ratio of deionized water to alcohol is 1 to 3:1; preferably, the cleaning times are 3 to 8 times;

[0037] Preferably, after cleaning the nano-reinforced tubes, the method further includes drying the reinforced tubes to obtain carbon nanotube-reinforced materials;

[0038] Preferably, the process of drying the reinforcement tube is: firstly drying naturally in air, and then drying in an air atmosphere at 100-200° C. for 0.5-4 hours.

[0039] According to another aspect of the present application, a composite material is provided, including a carbon nanotube reinforced material and a matrix material, wherein the carbon nanotube reinforced material is the above-mentioned carbon nanotube reinforced material; the matrix material is a metal matrix; preferably, the metal matrix includes one of an aluminum alloy and a magnesium alloy.

[0040] According to another aspect of the present application, there is provided a method for preparing the composite material as described above, comprising the following steps:

[0041] Step 1: Compounding the carbon nanotube reinforced material with the metal matrix to form a carbon nanotube reinforced metal matrix composite material;

[0042] In step 1, the nanotube-reinforced material is composited with a metal matrix to form a carbon nanotube-reinforced metal matrix composite material, including the following steps:

[0043] Step H1: mixing nanotube reinforcement material powder and metal powder to form mixed powder; ball milling the mixed powder to obtain composite material powder;

[0044] Step H2: forming a billet from the composite material powder;

[0045] Step H3: manufacturing the ingot into a carbon nanotube-reinforced metal matrix composite material.

[0046] Preferably, in step H2, forming the composite material powder into an ingot comprises the following steps:

[0047] Densification treatment is performed on the composite material powder to obtain a dense carbon nanotube-reinforced metal matrix composite material ingot; preferably, the densification treatment includes press molding and high-temperature sintering treatment;

[0048] And / or, in step H3, making the billet into a carbon nanotube-reinforced metal matrix composite material comprises the following steps: sequentially performing plastic working and heat treatment on the billet to obtain the carbon nanotube-reinforced metal matrix composite material; preferably, the plastic working comprises any one of hot extrusion, hot rolling and hot forging; preferably, the heat treatment comprises at least one of solution treatment and aging heat treatment;

[0049] and / or, the size of the metal powder is 10 to 60 μm;

[0050] And / or, in step H1, the ball milling treatment is performed under a protective gas environment; preferably, the protective gas is argon;

[0051] And / or, the ball-to-material ratio during the ball milling process is 5 to 15:1; the rotation speed is 100 to 400 rpm; and the ball milling time is 6 to 48 hours;

[0052] and / or, the process control agent in the ball milling process is at least one of stearic acid and petroleum ether;

[0053] And / or, in the mixed powder in step H1, the mass fraction of the nanotube reinforcement material is 2.0 to 6.0 wt.%.

[0054] The present application provides a carbon nanotube reinforced material and a preparation method thereof, a composite material and a preparation method thereof; the present application simultaneously utilizes the inner cavity and outer wall of the carbon nanotube, and by loading the corrosion inhibitor in the inner cavity and keeping the outer wall "clean", it gives it the dual functions of "inner cavity corrosion inhibition and outer wall reinforcement"; the present application can take into account both high strength and high corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a microscopic morphology of the carbon nanotubes with Na2MoO4 corrosion inhibitor loaded in the inner cavity of Example 1 of the present application.

[0056] Figure 2 This is a physical picture of an extruded rod of a 7085 aluminum-based composite material using a carbon nanotube reinforced material as a reinforcement phase in Example 6 of the present application.

[0057] Figure 3 The following is a comparison chart of the comprehensive matching performance of strength and corrosion resistance of the 7085 aluminum-based composite material using carbon nanotube reinforced material as the reinforcement phase in Example 6 of the present application with other aluminum alloys reported in the literature: (a) comprehensive matching performance of tensile strength and intergranular corrosion resistance, (b) comprehensive matching performance of tensile strength and exfoliation corrosion resistance. DETAILED DESCRIPTION

[0058] See also Figure 1-3 As shown, a carbon nanotube reinforced material includes carbon nanotubes; the carbon nanotubes are loaded with corrosion inhibitors; and the outer wall of the carbon nanotubes is a clean wall surface.

[0059] The clean wall surface mentioned in the present application is the original outer wall surface of the carbon nanotube, which is not contaminated with corrosion inhibitors, and its structure and characteristics have not changed at all; therefore, it still has the function of mechanical strengthening; and the corrosion inhibitor is loaded in the tube body, which can have high corrosion resistance; therefore, the present application can take into account both high strength and high corrosion resistance.

[0060] The carbon nanotubes of the present invention are open at both ends and are not soluble in water, but only form a suspension in an aqueous solution.

[0061] The present application utilizes both the inner cavity and outer wall of carbon nanotubes, and endows them with the dual functions of "inner cavity corrosion inhibition and outer wall strengthening" by loading the corrosion inhibitor in the inner cavity and keeping the outer wall "clean";

[0062] Compared with the traditional carbon nanotubes which only have the mechanical strengthening function, and the traditional nanocontainers loaded with corrosion inhibitors which only have the corrosion inhibition function and a small loading amount, the present application can take into account both high strength and high corrosion resistance.

[0063] When the ends of the carbon nanotube reinforced material of the present application are exposed to the corrosive medium, the corrosion inhibitor loaded inside it can be dissolved, forming a corrosion inhibitor film on the entire surface of the composite material, which can not only isolate the corrosive medium from contact with the metal, but also eliminate the difference between the reinforced material and the matrix, thereby greatly improving the corrosion resistance.

[0064] The present application also discloses some embodiments, wherein the corrosion inhibitor includes an inorganic corrosion inhibitor; the corrosion inhibitor may be a water-soluble corrosion inhibitor, which may form a mixed solution with the carbon nanotubes, and thus be loaded into the tube body of the carbon nanotubes.

[0065] The present application also discloses some embodiments, wherein the melting point of the corrosion inhibitor is higher than 680° C., which can ensure that the corrosion inhibitor does not melt during the preparation of the composite material.

[0066] The present application also discloses some embodiments, in which the inorganic corrosion inhibitor includes at least one of molybdate, tungstate, vanadate, etc.; these corrosion inhibitors generally have a relatively good corrosion protection effect on aluminum alloys, magnesium alloys, etc., and the melting points of sodium molybdate, potassium molybdate, sodium tungstate, and sodium vanadate are all higher than 680°C, which can ensure that they will not melt during the preparation of the composite material.

[0067] The present application also discloses some embodiments, wherein the carbon nanotubes include single-walled carbon nanotubes or multi-walled carbon nanotubes;

[0068] The present application also discloses some embodiments, in which the diameter of the carbon nanotube is less than 50nm; the length of the carbon nanotube is less than 50μm; if the diameter of the carbon nanotube used is too large (greater than or equal to 50nm), the plasticity of the composite material will be reduced; if the carbon nanotube is too long (length is equal to or greater than 50μm), the carbon nanotubes will be entangled with each other, which is not conducive to uniform dispersion.

[0069] The carbon nanotube reinforced material of the present application can have the corrosion inhibitor loaded in the inner cavity adjusted according to the type of metal matrix, and any currently used high melting point water-soluble inorganic corrosion inhibitor can be loaded, thus meeting the corrosion inhibition requirements of various metal-based composite materials.

[0070] The present application also discloses some embodiments, in which the mass of the corrosion inhibitor loaded in the carbon nanotube body is greater than 3 times the mass of the carbon nanotube body, which can ensure that the inner cavity of the carbon nanotube reinforced material is loaded with sufficient corrosion inhibitor to suppress the corrosion of the composite material.

[0071] According to an embodiment of the present application, a method for preparing the above-mentioned carbon nanotube reinforced material is also provided, comprising the following steps:

[0072] Step (1): loading a corrosion inhibitor into the carbon nanotube to obtain a nano-reinforced tube;

[0073] Step (2): Cleaning the nano-reinforced tubes to form a clean wall surface on the outer wall of the carbon nanotubes; obtaining a carbon nanotube reinforced material.

[0074] The preparation method of the carbon nanotube reinforced material of the present application is applicable to commercial carbon nanotubes and water-soluble corrosion inhibitors and has the capability of large-scale preparation.

[0075] The present application utilizes the special structure of carbon nanotubes with openings at both ends and a hollow interior as well as excellent mechanical properties, so that the inner cavity of the carbon nanotubes is loaded with a large amount of corrosion inhibitors while the outer wall is not contaminated, thereby ensuring that the inner cavity can inhibit corrosion by releasing corrosion inhibitors, and the outer wall can increase its strength through mechanisms such as load transfer, thereby achieving dual functional strengthening of inner cavity corrosion inhibition and outer wall reinforcement, thereby solving the difficult problem of the contradiction between high strength and high corrosion resistance of metal materials.

[0076] The present application also discloses some embodiments, in which in step (1), loading the carbon nanotube with a corrosion inhibitor comprises the following steps:

[0077] The purified carbon nanotubes and the corrosion inhibitor are uniformly mixed in water to form a mixed solution; the mixed solution is subjected to a boiling treatment to make the mixed solution boil, so that the purified carbon nanotubes are loaded with sufficient corrosion inhibitor, thereby enhancing the corrosion resistance.

[0078] The present application also discloses some embodiments, in which the mass ratio of the corrosion inhibitor to the purified carbon nanotubes in the mixed solution is greater than 4:1, which can ensure that the carbon nanotubes can be loaded with sufficient corrosion inhibitor, thereby enhancing the corrosion resistance.

[0079] The present application also discloses some embodiments, in which the purified carbon nanotubes and the corrosion inhibitor are uniformly mixed in water to form a mixed solution, which comprises the following steps: after mixing the purified carbon nanotubes and the corrosion inhibitor in water, stirring the solution under a constant temperature environment; the purpose of constant temperature stirring is to allow the inner cavity of the carbon nanotubes to load more corrosion inhibitor.

[0080] The present application also discloses some embodiments, the temperature of the constant temperature environment is 30-50°C; preferably, the constant temperature environment is controlled by an oil bath; preferably, the stirring includes the following steps: magnetic stirring is used, and the speed is controlled to be greater than 800 rpm. If the temperature is too low, the ion diffusion rate is slow, and the amount of corrosion inhibitor loaded in the inner cavity is small; if the temperature is too high, the solution is prone to boiling and splashing (the boiling point of the aqueous solution will decrease under a vacuum environment); oil bath heating can avoid water bath heating in a vacuum environment where water will boil, affecting the heating effect, and the boiling point of oil is high, so it will not boil in a vacuum environment; magnetic stirring is to make the carbon nanotubes disperse evenly, to ensure that as many carbon nanotube cavities as possible can load corrosion inhibitors, and to improve the loading efficiency; if the speed is too low, the dispersion effect is not good.

[0081] The present application also discloses some embodiments, wherein the method for preparing purified carbon nanotubes comprises the following steps: adding carbon nanotubes to a mixed solution of HNO3:H2SO4=1:2-4 and subjecting it to ultrasonic vibration, and then sequentially filtering the carbon nanotubes, washing the carbon nanotubes and drying the carbon nanotubes to obtain purified carbon nanotubes;

[0082] The present application also discloses some embodiments, wherein the ultrasonic oscillation time is 1 to 6 hours; the ultrasonic oscillation can make the carbon nanotubes dispersed evenly and make the purification more sufficient; within the ultrasonic oscillation time, the carbon nanotubes can be dispersed evenly to the greatest extent and purified sufficiently. If the ultrasonic oscillation time is too short, that is, the reaction time is too short, the degree of purification will be insufficient; if the time is too long, it will cause an overreaction, resulting in holes on the side walls of the carbon nanotubes, affecting the mechanical strengthening effect.

[0083] The present application also discloses some embodiments, in which, during the ultrasonic oscillation process, a constant temperature environment is provided, preferably, the temperature of the constant temperature environment is 30-60°C; preferably, the constant temperature environment is controlled by a water bath; the constant temperature is controlled so that the temperature is between 30 and 60°C, so that the reaction speed is moderate and the purification is appropriate, thereby ensuring the mechanical strengthening effect; if the temperature is too low, the reaction rate is slow and the degree of purification is insufficient; if the temperature is too high, the reaction rate is too fast, resulting in excessive purification, which affects the mechanical strengthening effect.

[0084] The present application also discloses some embodiments, in which the carbon nanotube cleaning process is to repeatedly rinse with deionized water until the filtrate is neutral; repeated cleaning until the filtrate is neutral can ensure that the mixed acid solution used for purification has been completely cleaned.

[0085] The present application also discloses some embodiments, wherein the temperature for drying the carbon nanotubes is 40 to 80°C; and the time for drying the carbon nanotubes is 1 to 3 hours. Drying the carbon nanotubes at the above temperature and time can fully dry the water in the carbon nanotubes. If the drying temperature is too low or the time is too short, the water cannot be completely volatilized; if the temperature is too high or the time is too long, no better drying effect will be produced.

[0086] The present application also discloses some embodiments, and the boiling treatment includes the following steps: Step S1: evacuating the container where the mixed solution is located to make the mixed solution boil; preferably, evacuating the container where the mixed solution is located includes the following steps: using a vacuum pump to evacuate the container to a pressure lower than -0.0950MPa; the present application adopts a vacuum adsorption method to load the corrosion inhibitor, and only when the pressure is lower than -0.0950MPa (high vacuum) can the solution boil. During the boiling process of the solution, the air in the inner cavity of the carbon nanotube will overflow, and the solution dissolved with the corrosion inhibitor can enter the cavity of the carbon nanotube and be adsorbed by the inner cavity to complete the loading.

[0087] The present application also discloses some embodiments, which further include the following steps after vacuuming the container where the mixed solution is located:

[0088] Step S2: performing pressure relief treatment on the container where the mixed solution is located; preferably, in step S2, performing pressure relief treatment on the container where the mixed solution is located comprises: releasing the pressure until the air pressure in the container is equal to the atmospheric pressure;

[0089] Step S3: Repeat step S1-step S2; repeatedly vacuumize-depressurize to completely remove the air in the carbon nanotube cavity, so that more solution containing the corrosion inhibitor can enter the carbon nanotube cavity, thereby increasing the loading amount of the corrosion inhibitor.

[0090] The atmospheric pressure is normal atmospheric pressure.

[0091] The present application also discloses some embodiments, in which the number of repetitions in step S3 is 3 to 30 times; the present application uses two key processes, constant temperature stirring and repeated vacuum (boiling)-pressure relief, to load the carbon nanotube inner cavity with a corrosion inhibitor more than 3 times its own mass, so that the carbon nanotube has a corrosion inhibition function;

[0092] The present application also discloses some embodiments, in which, in the last repetition process, the vacuum is maintained for 0 to 120 minutes before the pressure relief treatment is performed. Preferably, more corrosion inhibitors can be loaded in the carbon nanotubes.

[0093] The present application also discloses some embodiments, which further include the following steps after step (1) and before step (2):

[0094] Filtering the mixed solution after the treatment in step S3 to obtain a nano-enhanced tube filter residue;

[0095] The present application also discloses some embodiments, wherein filtering the mixed solution after the treatment in step S3 comprises the following steps: filtering the mixed solution with filter paper or filter membrane to obtain nano-enhanced tube filter residue, wherein the filter residue comprises nano-enhanced tubes;

[0096] The present application also discloses some embodiments, in which in step (2), cleaning the nano-enhanced tubes comprises the following steps:

[0097] The nano-enhanced tubes are cleaned with a mixed solution of alcohol and water; preferably, the water is deionized water; preferably, the volume ratio of deionized water to alcohol is 1 to 3:1; preferably, the cleaning frequency is 3 to 8 times; deionized water can dissolve the corrosion inhibitor attached to the outer wall, and the alcohol can be quickly preliminarily dried during the cleaning process to avoid secondary attachment. Only by repeated cleaning with a mixed solution of deionized water and alcohol can the outer wall of the carbon nanotube be cleaned; the cleaning frequency is 3 to 8 times to effectively clean the outer wall without affecting the corrosion inhibitor in the carbon nanotube; if the deionized water is too little or the cleaning frequency is too little, the outer wall will not be cleaned cleanly; if the deionized water is too much or the cleaning frequency is too little, the corrosion inhibitor loaded in the inner cavity will also be dissolved out, not only the outer wall will not be cleaned cleanly, but also the corrosion inhibitor loaded in the inner cavity will be lost.

[0098] The present application also discloses some embodiments, which further include drying the nano-reinforced tubes after cleaning to obtain carbon nano-tube reinforced materials;

[0099] The present application also discloses some embodiments, and the process of the enhanced tube drying treatment is: first, naturally dry in the air, and then dry in an air atmosphere of 100-200°C for 0.5-4 hours. Impurities and crystal water are removed by two key processes: washing with an alcohol / water mixed solution and high-temperature drying, so that the outer wall of the carbon nanotube is not contaminated during the process of loading the corrosion inhibitor, that is, the outer wall of the carbon nanotube is a clean wall surface, which can still play a mechanical strengthening function through mechanisms such as load transfer. The dried carbon nanotube has the dual function of simultaneously improving the strength and corrosion resistance of metal materials. Natural drying can quickly remove the cleaning solution (a mixed solution of water and alcohol), and high-temperature drying (drying at 100-200°C) can remove the crystal water attached to the outer wall of the carbon nanotube; if the temperature is too low or the time is too short, the crystal water is not removed cleanly; if the temperature is too high or the time is too long, it will not produce a better effect of removing the crystal water. In order to improve efficiency, it is not necessary to use a higher temperature or a longer time.

[0100] The present application utilizes the special structure of carbon nanotubes with openings at both ends and a hollow interior as well as excellent mechanical properties. Through four key operations, namely constant temperature stirring, repeated vacuum (boiling)-pressure relief, alcohol / water mixed solution cleaning and high-temperature drying, the inner cavity of the carbon nanotubes is loaded with a large amount of corrosion inhibitor while the outer wall is not contaminated, thereby ensuring that the inner cavity can inhibit corrosion by releasing the corrosion inhibitor and the outer wall can increase strength by transferring the load, thereby achieving dual functional enhancement of inner cavity corrosion inhibition and outer wall reinforcement, thereby solving the difficult problem of the contradiction between high strength and high corrosion resistance of metal materials.

[0101] The preparation method of the carbon nanotube reinforced material of the present application does not change the characteristics of the carbon nanotube outer wall, that is, the function of the carbon nanotube outer wall to strengthen through the mechanism of transferring load and the interface bonding between the outer wall and the metal matrix will not be affected. The preparation method of the carbon nanotube reinforced material of the present application avoids the cost of a lot of manpower, material resources and time to explore the preparation process parameters of new high-strength and high-corrosion-resistant metal-based composite materials, and greatly shortens the development cycle of such new materials.

[0102] According to an embodiment of the present application, a composite material is also provided, including a carbon nanotube reinforced material and a matrix material, wherein the carbon nanotube reinforced material is the above-mentioned carbon nanotube reinforced material; the matrix material is a metal matrix; preferably, the metal matrix includes one of an aluminum alloy and a magnesium alloy.

[0103] The carbon nanotubes with inner cavity loaded with corrosion inhibitors prepared in the present application, i.e., carbon nanotube reinforced materials, can be used as dual-functional reinforcing phases and can be applied to metal-based composite materials. The inner cavity can realize the corrosion inhibition function by releasing corrosion inhibitors, and the outer wall can realize the mechanical strengthening function through mechanisms such as load transfer, thereby simultaneously improving the strength and corrosion resistance of the metal-based composite materials, and can realize "self-corrosion inhibition" throughout the entire life cycle.

[0104] According to an embodiment of the present application, a method for preparing the composite material as described above is also provided, comprising the following steps:

[0105] Step 1: Compounding the carbon nanotube reinforced material with the metal matrix to form a carbon nanotube reinforced metal matrix composite material;

[0106] In step 1, the nanotube-reinforced material is composited with a metal matrix to form a carbon nanotube-reinforced metal matrix composite material, including the following steps:

[0107] Step H1: mixing nanotube reinforcement material powder and metal powder to form mixed powder; ball milling the mixed powder to obtain composite material powder;

[0108] Step H2: forming a billet from the composite material powder;

[0109] Step H3: manufacturing the ingot into a carbon nanotube-reinforced metal matrix composite material.

[0110] The present application also discloses some embodiments, in which in step H2, forming a billet from the composite material powder comprises the following steps:

[0111] Densification treatment is performed on the composite material powder to obtain a dense carbon nanotube-reinforced metal matrix composite material ingot; preferably, the densification treatment includes press molding and high-temperature sintering treatment;

[0112] The present application also discloses some embodiments, in step H3, making the billet into a carbon nanotube-reinforced metal matrix composite material comprises the following steps: sequentially performing plastic processing and heat treatment on the billet to obtain the carbon nanotube-reinforced metal matrix composite material; preferably, the plastic processing comprises any one of hot extrusion, hot rolling, and hot forging; preferably, the heat treatment comprises at least one of solution treatment and aging heat treatment;

[0113] The present application also discloses some embodiments, in which the size of the metal powder is 10 to 60 μm; at this size, the excellent mechanical properties of the present application can be achieved without causing embrittlement of the composite material; if the particle size of the metal powder is too small, the composite material will become embrittled, which is detrimental to the mechanical properties; if the metal powder is too large, the particle size of the ball-milled powder will be uneven, which is detrimental to the mechanical properties; in addition, a particle size that is too small or too large will lead to an increase in the powder cost.

[0114] The present application also discloses some embodiments, in which, in step H1, the ball milling process is performed in a protective gas environment to prevent oxidation of the metal powder during the ball milling process.

[0115] Preferably, the protective gas is argon gas, and the argon gas is high-purity argon gas. The use of argon gas protection can prevent the metal powder from being oxidized during the ball milling process.

[0116] The present application also discloses some embodiments, in which the ball-to-material ratio in the ball milling process is 5 to 15:1; the rotation speed is 100 to 400 rpm; the ball milling time is 6 to 48 hours; the ball milling process adopts the above-mentioned ball-to-material ratio, rotation speed and time control to ensure that the powder and carbon nanotubes are mixed evenly, and at the same time, the carbon nanotubes are prevented from being damaged during the ball milling process, resulting in corrosion inhibitor overflow. If the ball-to-material ratio is too small, the rotation speed is too low, and the ball milling time is too short, it is not conducive to the uniform dispersion of carbon nanotubes and the uniform mixing of metal powders; if the ball-to-material ratio is too large, the rotation speed is too high, and the ball milling time is too long, on the one hand, it will cause carbon nanotube damage and corrosion inhibitor overflow, and on the other hand, it is easy to cause interface reaction, which is not conducive to mechanical properties.

[0117] The present application also discloses some embodiments, in which the process control agent in the ball milling process is at least one of stearic acid and petroleum ether; using stearic acid and / or petroleum ether can make the carbon nanotubes dispersed evenly.

[0118] The present application also discloses some embodiments, in which the mass fraction of the nanotube reinforcement material in the mixed powder in step H1 is 2.0-6.0wt.%. Within the above mass fraction range, the mechanical properties and corrosion inhibition effect of the composite material can be guaranteed; if the mass fraction of the carbon nanotube reinforcement material is too small, the mechanical strengthening and corrosion inhibition effect of the composite material will be insufficient; if the mass fraction is too high, the plasticity of the composite material will be sharply reduced, which is not conducive to the mechanical properties.

[0119] Example

[0120] In the following embodiments, the mechanical properties test refers to GB / T228.1-2010 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method"; the corrosion rate test in 3.5wt.% solution refers to GB / T10124-88 "Laboratory Uniform Corrosion Full Immersion Test Method for Metallic Materials"; the intergranular corrosion depth test refers to GB / T7998-2005 "Determination Method for Intergranular Corrosion of Aluminum Alloys"; the exfoliation corrosion grade test refers to GB / T40338-2021 "Corrosion of Metals and Alloys-Aluminum Alloy Exfoliation Corrosion Test".

[0121] Example 1

[0122] In this embodiment, bifunctional multi-walled carbon nanotubes with Na2MoO4 corrosion inhibitor loaded in the inner cavity are prepared, and the main preparation steps are as follows:

[0123] Multi-walled carbon nanotubes with a diameter of 15 to 30 nm and a length of 15 to 30 μm are placed in a mixed solution of HNO3:H2SO4=1:2, ultrasonically vibrated at 30°C for 6 hours, filtered and dried at 80°C for 1 hour to obtain purified carbon nanotubes; Na2MoO4 corrosion inhibitor with a mass ratio of 6:1 and purified carbon nanotubes are evenly mixed in water to form a suspension, and evacuated to a pressure of -0.0985 MPa at a temperature of 30°C and a rotation speed of 900 rpm to boil the solution, and then the pressure is released to normal pressure, and the above vacuum-pressure release operation is repeated 30 times; after the last pressure release operation, the mixed solution is filtered, and the filter residue is repeatedly washed 3 times with a solution with a volume ratio of deionized water and alcohol of 3:1, the filter residue is naturally dried in the air, and finally dried in an air atmosphere at 200°C for 0.5 hour to obtain a bifunctional multi-walled carbon nanotube with a large amount of Na2MoO4 corrosion inhibitor loaded in the inner cavity and no pollution on the outer wall.

[0124] ( Figure 1 As shown, the outer wall of the carbon nanotubes after loading the corrosion inhibitor is smooth, and no pollutants are observed; the inner cavity is filled with dark substances, and the energy spectrum analysis results show that it contains a large amount of Mo, Na, and O elements, which can be determined to be loaded Na2MoO4 corrosion inhibitor). The amount of Na2MoO4 corrosion inhibitor loaded in the inner cavity is as high as 3850 mg / g.

[0125] Example 2

[0126] In this embodiment, bifunctional multi-walled carbon nanotubes with Na2MoO4 corrosion inhibitor loaded in the inner cavity are prepared, and the main preparation steps are as follows:

[0127] Multi-walled carbon nanotubes with a diameter of 50 nm and a length of 50 μm were placed in a mixed solution of HNO3:H2SO4=1:4, and ultrasonically vibrated at 60°C for 1 hour. After filtering, they were dried at 40°C for 3 hours to obtain purified carbon nanotubes. Na2MoO4 corrosion inhibitor with a mass ratio of 5:1 and purified carbon nanotubes were mixed in water to form a suspension. Under the conditions of temperature of 50°C and rotation speed of 1000 rpm, the pressure was evacuated to -0.0970 MPa, and the solution was boiled, and then The pressure was released to normal pressure, and the above vacuum-pressure release operation was repeated 3 times; after the last pressure release operation, the mixed solution was filtered, and the filter residue was repeatedly washed 8 times with a solution of deionized water and alcohol in a volume ratio of 1:1, the filter residue was naturally dried in the air, and finally dried at 100°C in an air atmosphere for 4 hours to obtain bifunctional multi-walled carbon nanotubes with a large amount of Na2MoO4 corrosion inhibitor loaded in the inner cavity and no pollution on the outer wall. The amount of Na2MoO4 corrosion inhibitor loaded in the inner cavity was as high as 3380 mg / g.

[0128] Example 3

[0129] In this embodiment, bifunctional multi-walled carbon nanotubes with Na2WO4 corrosion inhibitor loaded in the inner cavity are prepared, and the main preparation steps are as follows:

[0130] Multi-walled carbon nanotubes with a diameter of 15 to 30 nm and a length of 15 to 30 μm were placed in a mixed solution of HNO3:H2SO4=1:3, ultrasonically shaken at 40°C for 4 hours, filtered and dried at 60°C for 2 hours to obtain purified carbon nanotubes; Na2WO4 corrosion inhibitor with a mass ratio of 7:1 and purified carbon nanotubes were mixed evenly in water to form a suspension, and vacuumed to a pressure of -0.0980 MPa at a temperature of 35°C and a rotation speed of 1000 rpm to boil the solution, and then the pressure was released to normal pressure, and the above vacuuming-pressure release operation was repeated. The process was repeated 25 times; in the last vacuuming-depressurizing operation, the pressure was evacuated to -0.0980 MPa and maintained for 120 minutes, and then the pressure was released to normal pressure; the mixed solution was then filtered, and the filter residue was repeatedly washed 5 times with a solution of deionized water and alcohol in a volume ratio of 2:1, the filter residue was naturally dried in the air, and finally dried at 150°C in an air atmosphere for 3 hours to obtain bifunctional multi-walled carbon nanotubes with a large amount of Na2WO4 corrosion inhibitor loaded in the inner cavity and no pollution on the outer wall, and the amount of Na2WO4 corrosion inhibitor loaded in the inner cavity was as high as 3805 mg / g.

[0131] Example 4

[0132] In this embodiment, bifunctional multi-walled carbon nanotubes with Na3VO4 corrosion inhibitor loaded in the inner cavity are prepared, and the main preparation steps are as follows:

[0133] Multi-walled carbon nanotubes with a diameter of 15 to 30 nm and a length of 15 to 30 μm were placed in a mixed solution of HNO3:H2SO4=1:4, and ultrasonically vibrated at 50°C for 3 hours. After filtering, the mixture was dried at 50°C for 2.5 hours to obtain purified carbon nanotubes. Na3VO4 corrosion inhibitor with a mass ratio of 7:1 and purified carbon nanotubes were mixed in water to form a suspension. The suspension was evacuated to a vacuum degree of -0.0975 MPa at a temperature of 50°C and a rotation speed of 900 rpm to boil the solution, and then the pressure was released to normal pressure. The above-mentioned evacuation-pressure release was repeated. The operation was repeated 20 times; in the last vacuuming-depressurization operation, the vacuum degree was evacuated to -0.0975 MPa and maintained for 30 minutes, and then the pressure was released to return to normal pressure; the mixed solution was then filtered, and the filter residue was repeatedly washed 6 times with a solution of deionized water and alcohol in a volume ratio of 3:1, the filter residue was naturally dried in the air, and finally dried at 200°C in an air atmosphere for 3 hours to obtain bifunctional multi-walled carbon nanotubes with a large amount of Na3VO4 corrosion inhibitor loaded in the inner cavity and no pollution on the outer wall, and the amount of Na3VO4 corrosion inhibitor loaded in the inner cavity was as high as 3728 mg / g.

[0134] Example 5

[0135] In this embodiment, dual-functional single-walled carbon nanotubes with Na2MoO4 corrosion inhibitor loaded in the inner cavity are prepared, and the main preparation steps are as follows:

[0136] Single-walled carbon nanotubes with a diameter of 0.8 to 1.2 nm and a length of 15 to 30 μm were placed in a mixed solution of HNO3:H2SO4=1:2, ultrasonically shaken at 45°C for 6 hours, filtered and dried at 60°C for 2 hours to obtain purified carbon nanotubes; Na2MoO4 corrosion inhibitor with a mass ratio of 6:1 and purified carbon nanotubes were mixed in water to form a suspension, and vacuumed to a vacuum degree of -0.0990 MPa at a temperature of 30°C and a rotation speed of 1000 rpm to boil the solution, and then the pressure was released to normal pressure, and the above vacuuming-pressure release was repeated. The operation was performed 30 times. In the last vacuuming-depressurization operation, the vacuum degree was evacuated to -0.0990 MPa and maintained for 30 minutes, and then the pressure was released to return to normal pressure. The mixed solution was then filtered, and the filter residue was repeatedly washed 4 times with a solution of deionized water and alcohol in a volume ratio of 1:1. The filter residue was naturally dried in the air and finally dried at 200°C in an air atmosphere for 2 hours to obtain bifunctional single-walled carbon nanotubes with a large amount of Na2MoO4 corrosion inhibitor loaded in the inner cavity and no pollution on the outer wall. The amount of Na2MoO4 corrosion inhibitor loaded in the inner cavity was as high as 3556 mg / g.

[0137] Embodiment 6:

[0138] In this embodiment, the bifunctional carbon nanotubes prepared in Example 1 are used to prepare a high-strength and high-corrosion-resistant 7085 aluminum-based composite material. The main preparation steps are as follows:

[0139] 7085 aluminum alloy powder (pure metal mixed powder, with a composition ratio of Zn7.50wt.%, Mg2.80wt.%, Cu1.40wt.%, and Al balance) with an average size of 34μm and 4.0wt.% of bifunctional carbon nanotubes with an inner cavity loaded with Na2MoO4 corrosion inhibitor prepared in Example 1 were added into a ball mill, and grinding balls were added according to a ball-to-material ratio of 5:1. 2.0wt% of stearic acid was added as a process control agent, and high-purity argon gas was introduced. The mixture was ball milled at 400 rpm for 24 hours to obtain a uniformly dispersed composite material powder. The composite material powder was cold pressed at 50MPa, and then vacuumed at 10 -2 Pa, hot pressing and sintering at 520°C for 2 hours to obtain a composite material ingot; the composite material ingot was hot extruded at 420°C with an extrusion ratio of 17:1 to obtain a 4.0wt.% bifunctional carbon nanotube / 7085 aluminum-based composite material rod ( Figure 2 ); The composite material was solution treated at 470°C for 50 minutes, rapidly quenched in water and then artificially aged at 120°C for 24 hours to obtain a high-strength and high-corrosion-resistant 4.0wt.% bifunctional carbon nanotube-reinforced 7085 aluminum-based composite material.

[0140] The composite material has a yield strength of 745MPa, a tensile strength of 785MPa, and an elongation of about 4.2%. The average corrosion rate in a 3.5wt.% NaCl solution at 25°C is 0.0023mm / a, the intergranular corrosion depth is 3.4μm, and the exfoliation corrosion grade is N. The composite material has a comprehensive matching performance of strength and corrosion resistance that exceeds that of other aluminum alloys and aluminum-based composite materials in the prior art ( Figure 3 ), which has a good application prospect.

[0141] Embodiment 7:

[0142] In this embodiment, the bifunctional carbon nanotubes prepared in Example 2 are used to prepare a high-strength and high-corrosion-resistant 7075 aluminum-based composite material. The main preparation steps are as follows:

[0143] 7075 aluminum alloy powder with an average size of 31 μm (alloy powder, composition ratio of Zn5.60wt.%, Mg2.76wt.%, Cu1.42wt.%, Al balance) and 2.0wt.% of bifunctional carbon nanotubes with inner cavity loaded Na2MoO4 corrosion inhibitor prepared in Example 1 were added into a ball mill, grinding balls were added according to a ball-to-material ratio of 15:1, and 2.0wt% of stearic acid was added as a process control agent, high-purity argon was introduced, and ball milling was performed at 100 rpm for 48 hours to obtain a uniformly dispersed composite material powder; the composite material powder was cold pressed at 60MPa, and then vacuum 10 -2The composite material ingot was hot pressed and sintered at a temperature of 520°C for 2 hours to obtain a composite material ingot; the composite material ingot was hot extruded at 450°C with an extrusion ratio of 17:1 to obtain a 2.0wt.% bifunctional carbon nanotube / 7075 aluminum-based composite material rod; the composite material was solution treated at 475°C for 60 minutes, rapidly water quenched and then artificially aged at 120°C for 24 hours to obtain a high-strength and high-corrosion-resistant 2.0wt.% bifunctional carbon nanotube-reinforced 7075 aluminum-based composite material.

[0144] The yield strength of the composite material reaches 690MPa, the tensile strength reaches 725MPa, and the elongation is about 3.8%; the average corrosion rate in 3.5wt.% NaCl solution at 25°C is 0.035mm / a, the intergranular corrosion depth is 6.1μm, and the exfoliation corrosion grade is P. The composite material has excellent high strength and high corrosion resistance comprehensive matching performance and has a good application prospect.

[0145] Embodiment 8:

[0146] In this embodiment, the bifunctional carbon nanotubes prepared in Example 3 are used to prepare a high-strength and high-corrosion-resistant 2024 aluminum-based composite material, and the main preparation steps are as follows:

[0147] 2024 aluminum alloy powder (pure metal mixed powder, with a composition ratio of Mg1.40wt.%, Cu3.90wt.%, and Al as the balance) with an average size of 10μm and 4.0wt.% of the bifunctional carbon nanotubes with an inner cavity loaded with Na2WO4 corrosion inhibitor prepared in Example 3 were added into a ball mill, and grinding balls were added according to a ball-to-material ratio of 10:1. 2.0wt% of petroleum ether was added as a process control agent, and high-purity argon was introduced. The mixture was ball milled at 300 rpm for 20 hours to obtain a uniformly dispersed composite material powder. The composite material powder was cold pressed at 70MPa, and then vacuumed at 10 -2 The composite material ingot was hot pressed and sintered at a temperature of 540°C for 1.5 hours to obtain a composite material ingot; the composite material ingot was hot extruded at 450°C with an extrusion ratio of 15:1 to obtain a 4.0wt.% bifunctional carbon nanotube / 2024 aluminum-based composite material rod; the composite material was solution treated at 500°C for 60 minutes, quickly water quenched and then naturally aged at room temperature for 24 hours to obtain a high-strength and high-corrosion-resistant 4.0wt.% bifunctional carbon nanotube-reinforced 2024 aluminum-based composite material.

[0148] The yield strength of the composite material reaches 600MPa, the tensile strength reaches 675MPa, and the elongation is about 4.0%; the average corrosion rate in 3.5wt.% NaCl solution at 25°C is 0.083mm / a, the intergranular corrosion depth is 7.9μm, and the exfoliation corrosion grade is P. The composite material has excellent high strength and high corrosion resistance comprehensive matching performance and has a good application prospect.

[0149] Embodiment 9:

[0150] In this embodiment, the bifunctional carbon nanotubes prepared in Example 4 are used to prepare a high-strength and high-corrosion-resistant 6061 aluminum-based composite material, and the main preparation steps are as follows:

[0151] 6061 aluminum alloy powder (pure metal mixed powder, with a composition ratio of Si0.6wt%, Mg1.20wt%, Cu0.20wt%, and Al balance) with an average size of 60μm and 6.0wt% of bifunctional carbon nanotubes with an inner cavity loaded with Na3VO4 corrosion inhibitor prepared in Example 4 were added into a ball mill, and grinding balls were added according to a ball-to-material ratio of 7:1. 2.0wt% of stearic acid was added as a process control agent, and high-purity argon gas was introduced. The mixture was ball milled at 400 rpm for 6 hours to obtain a uniformly dispersed composite material powder. The composite material powder was cold pressed at 80MPa, and then vacuumed at 10 -2 The composite material ingot was hot pressed and sintered at a temperature of 540°C for 1.5 hours to obtain a composite material ingot; the composite material ingot was hot extruded at 450°C with an extrusion ratio of 18:1 to obtain a 6.0wt.% bifunctional carbon nanotube / 6061 aluminum-based composite material rod; the composite material was solution treated at 480°C for 60 minutes, quickly water quenched and then artificially aged at 120°C for 24 hours to obtain a high-strength and high-corrosion-resistant 6.0wt.% bifunctional carbon nanotube-reinforced 6061 aluminum-based composite material.

[0152] The yield strength of the composite material reaches 415MPa, the tensile strength reaches 455MPa, and the elongation is about 15.0%. The average corrosion rate in 3.5wt.% NaCl solution is 0.048mm / a, and the intergranular corrosion depth is 7.5μm. The composite material has excellent high strength and high corrosion resistance comprehensive matching performance and has a good application prospect.

[0153] Embodiment 10:

[0154] In this example, the bifunctional carbon nanotubes prepared in Example 5 are used to prepare a high-strength and high-corrosion-resistant 7075 aluminum-based composite material. The main preparation steps are as follows:

[0155] 7075 aluminum alloy powder with an average size of 31 μm (alloy powder, composition ratio of Zn5.60wt.%, Mg2.76wt.%, Cu1.42wt.%, Al balance) and 5.0wt.% of bifunctional carbon nanotubes with inner cavity loaded Na2MoO4 corrosion inhibitor prepared in Example 5 were added into a ball mill, grinding balls were added according to a ball-to-material ratio of 10:1, and 2.0wt% of stearic acid was added as a process control agent, high-purity argon was introduced, and ball milling was performed at 200 rpm for 24 hours to obtain a uniformly dispersed composite material powder; the composite material powder was cold pressed at 60MPa, and then vacuum 10 -2Pa, hot pressing and sintering at a temperature of 520°C for 2 hours to obtain a composite material ingot; the composite material ingot is hot extruded at 450°C with an extrusion ratio of 17:1 to obtain a 5.0wt.% bifunctional carbon nanotube / 7075 aluminum-based composite material rod; the composite material is solution treated at 480°C for 60 minutes, rapidly water quenched and then artificially aged at 120°C for 24 hours to obtain a high-strength and high-corrosion-resistant 5.0wt.% bifunctional carbon nanotube-reinforced 7075 aluminum-based composite material.

[0156] The yield strength of the composite material reaches 672MPa, the tensile strength reaches 695MPa, and the elongation is about 4.1%; the average corrosion rate in 3.5wt.% NaCl solution at 25°C is 0.069mm / a, the intergranular corrosion depth is 10.3μm, and the exfoliation corrosion grade is P. The composite material has excellent high strength and high corrosion resistance comprehensive matching performance and has a good application prospect.

[0157] Embodiment 11:

[0158] In this example, the bifunctional carbon nanotubes prepared in Example 3 are used to prepare a high-strength and high-corrosion-resistant AZ31 magnesium-based composite material. The main preparation steps are as follows:

[0159] AZ31 magnesium alloy powder (pure metal mixed powder, with a composition ratio of Al3.1wt%, Zn1.0wt%, Mn0.3wt%, and Mg balance) with an average size of 35μm and 4.0wt% of bifunctional carbon nanotubes with an inner cavity loaded with Na2WO4 corrosion inhibitor prepared in Example 3 were added to a ball mill, and grinding balls were added according to a ball-to-material ratio of 10:1. 2.0wt% of stearic acid was added as a process control agent, and high-purity argon gas was introduced. The mixture was ball milled at 150 rpm for 16 hours to obtain a uniformly dispersed composite material powder. The composite material powder was cold pressed at 50MPa, and then vacuumed at 10 -2 Pa, hot pressing and sintering at a temperature of 580°C for 50 minutes to obtain a composite material ingot; the composite material ingot is hot extruded at 360°C with an extrusion ratio of 9:1 to obtain a 4.0wt.% bifunctional carbon nanotube / AZ31 magnesium-based composite material rod; the composite material is solution treated at 420°C for 10 hours, rapidly water quenched and then artificially aged at 200°C for 6 hours to obtain a high-strength and high-corrosion-resistant 4.0wt.% bifunctional carbon nanotube-reinforced AZ31 magnesium-based composite material.

[0160] The yield strength of the composite material reaches 284MPa, the tensile strength reaches 324MPa, and the elongation is about 3.5%. The average corrosion rate in 3.5wt.% NaCl solution at 25°C is 0.096mm / a. The composite material has excellent high strength and high corrosion resistance comprehensive matching performance and has a good application prospect.

[0161] Comparative Example 1:

[0162] Compared with Example 6, the difference is that only purified multi-walled carbon nanotubes (without corrosion inhibitor loaded in the inner cavity) are used as the reinforcing phase, and the other preparation process and parameters are the same. The yield strength of the prepared traditional carbon nanotube reinforced 7085 aluminum-based composite material is 740MPa, the tensile strength is 790MPa, and the elongation is about 4.3%; the average corrosion rate in 3.5wt.% NaCl solution at 25°C is 7.895mm / a, the intergranular corrosion depth is 335μm, and the exfoliation corrosion grade is ED grade. Its mechanical properties are comparable to those of the high-strength and high-corrosion-resistant dual-functional carbon nanotube reinforced 7085 aluminum-based composite material prepared in Example 6, but the corrosion resistance is significantly reduced.

[0163] Comparative Example 2:

[0164] Compared with Example 7, the difference is that only purified multi-walled carbon nanotubes (without corrosion inhibitor loaded in the inner cavity) are used as the reinforcing phase, and the other preparation process and parameters are the same. The yield strength of the prepared traditional carbon nanotube reinforced 7075 aluminum-based composite material is 693MPa, the tensile strength is 732MPa, and the elongation is about 3.9%; the average corrosion rate in 3.5wt.% NaCl solution at 25°C is 6.538mm / a, the intergranular corrosion depth is 301μm, and the exfoliation corrosion grade is EC grade. Its mechanical properties are comparable to those of the high-strength and high-corrosion-resistant dual-functional carbon nanotube reinforced 7075 aluminum-based composite material prepared in Example 7, but the corrosion resistance is significantly reduced.

[0165] Comparative Example 3:

[0166] Compared with Example 8, the difference is that only purified multi-walled carbon nanotubes (without corrosion inhibitor loaded in the inner cavity) are used as the reinforcing phase, and the other preparation process and parameters are the same. The yield strength of the prepared traditional carbon nanotube reinforced 2024 aluminum-based composite material is 647MPa, the tensile strength is 683MPa, and the elongation is about 4.3%; the average corrosion rate in 3.5wt.% NaCl solution at 25°C is 1.186mm / a, the intergranular corrosion depth is 253μm, and the exfoliation corrosion grade is EC grade. Its mechanical properties are comparable to those of the high-strength and high-corrosion-resistant dual-functional carbon nanotube reinforced 2024 aluminum-based composite material prepared in Example 8, but the corrosion resistance is significantly reduced.

[0167] Comparative Example 4:

[0168] Compared with Example 9, the difference is that only purified multi-walled carbon nanotubes (without corrosion inhibitor loaded in the inner cavity) are used as the reinforcing phase, and the other preparation process and parameters are the same. The yield strength of the prepared traditional carbon nanotube reinforced 6061 aluminum-based composite material is 426MPa, the tensile strength is 464MPa, and the elongation is about 15.6%; the average corrosion rate in 3.5wt.% NaCl solution is 1.107mm / a, and the intergranular corrosion depth is 220μm. Its mechanical properties are comparable to those of the high-strength and high-corrosion-resistant dual-functional carbon nanotube reinforced 6061 aluminum-based composite material prepared in Example 9, but the corrosion resistance is significantly reduced.

[0169] Comparative Example 5:

[0170] Compared with Example 10, the difference is that only purified single-walled carbon nanotubes (without corrosion inhibitor loaded in the inner cavity) are used as the reinforcing phase, and the other preparation process and parameters are the same. The yield strength of the prepared traditional carbon nanotube reinforced 7075 aluminum-based composite material is 680MPa, the tensile strength is 703MPa, and the elongation is about 3.8%; the average corrosion rate in 3.5wt.% NaCl solution at 25°C is 6.028mm / a, the intergranular corrosion depth is 253μm, and the exfoliation corrosion grade is EC grade. Its mechanical properties are comparable to those of the high-strength and high-corrosion-resistant dual-functional carbon nanotube reinforced 7075 aluminum-based composite material prepared in Example 10, but the corrosion resistance is significantly reduced.

[0171] Comparative Example 6:

[0172] Compared with Example 11, the difference is that only purified single-walled carbon nanotubes (without corrosion inhibitor loaded in the inner cavity) are used as the reinforcing phase, and the other preparation process and parameters are the same. The yield strength of the prepared traditional carbon nanotube reinforced AZ31 magnesium-based composite material is 293MPa, the tensile strength is 330MPa, and the elongation is about 3.6%; the average corrosion rate in a 3.5wt.% NaCl solution at 25°C is 12.236mm / a. Its mechanical properties are comparable to those of the high-strength and high-corrosion-resistant dual-functional carbon nanotube reinforced AZ31 magnesium-based composite material prepared in Example 11, but the corrosion resistance is significantly reduced.

[0173] Comparative Example 7:

[0174] The carbon nanotube reinforced material was prepared according to the process parameters of Example 1, except that the constant temperature stirring was not performed during the vacuum-pressure relief operation (the temperature was room temperature, no stirring), and the other parameters were the same as those of Example 1. The amount of Na2MoO4 corrosion inhibitor loaded in its inner cavity was only 35 mg / g, which was significantly lower than 3850 mg / g in Example 1. Using it as a reinforcing phase, the same process flow and parameters as Example 6 were used to prepare a carbon nanotube-reinforced 7085 aluminum-based composite material, with a yield strength of 742 MPa, a tensile strength of 788 MPa, and an elongation of about 4.1%; the average corrosion rate in a 3.5wt.% NaCl solution at 25°C was 5.860 mm / a, the intergranular corrosion depth was 293 μm, and the exfoliation corrosion grade was EC. Its mechanical properties were comparable to those of the high-strength and high-corrosion-resistant dual-functional carbon nanotube-reinforced 7085 aluminum-based composite material prepared in Example 6, but its corrosion resistance was significantly reduced.

[0175] Comparative Example 8:

[0176] The carbon nanotube reinforced material was prepared according to the process parameters of Example 1, except that the vacuum was evacuated to -0.080MPa during the preparation process, and the solution did not boil. The other parameters were the same as those of Example 1. The amount of Na2MoO4 corrosion inhibitor loaded in its inner cavity was only 620mg / g, which was significantly lower than 3850mg / g in Example 1. Using it as a reinforcing phase, the same process flow and parameters as Example 6 were used to prepare a carbon nanotube-reinforced 7085 aluminum-based composite material, with a yield strength of 738MPa, a tensile strength of 782MPa, and an elongation of about 4.1%; the average corrosion rate in a 3.5wt.% NaCl solution at 25°C was 3.258mm / a, the intergranular corrosion depth was 159μm, and the exfoliation corrosion grade was EA. Its mechanical properties were comparable to those of the high-strength and high-corrosion-resistant dual-functional carbon nanotube-reinforced 7085 aluminum-based composite material prepared in Example 6, but its corrosion resistance was significantly reduced.

[0177] Comparative Example 9:

[0178] The carbon nanotube reinforced material was prepared according to the process parameters of Example 1, except that after the corrosion inhibitor was loaded, only the outer wall was cleaned with water and dried at 80°C, and the other parameters were the same as those of Example 1. The amount of Na2MoO4 corrosion inhibitor loaded in its inner cavity was 3862 mg / g, which was equivalent to the 3850 mg / g loading amount of Example 1. It was used as a reinforcing phase, and the same process flow and parameters as Example 6 were used to prepare a carbon nanotube-reinforced 7085 aluminum-based composite material. The material cracked after hot pressing and sintering and could not be formed. The reason is that cleaning the outer wall with water and low-temperature drying cannot ensure the cleanliness of the outer wall of the carbon nanotube, which significantly reduces the interfacial bonding force between the carbon nanotube and the aluminum alloy matrix, and ultimately causes the composite material to be unable to be formed.

[0179] The comprehensive matching of strength and corrosion resistance of the composite material using the carbon nanotube reinforced material of the present application as the reinforcement phase exceeds that of similar composite materials currently known, and effectively solves the problem of the contradiction between high strength and high corrosion resistance of metal materials.

[0180] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed.

[0181] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application shall be included in the protection scope of the present application. The above are only preferred implementations of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A method for preparing a carbon nanotube reinforced material, characterized in that: The steps include: Step (1): loading a corrosion inhibitor into the carbon nanotube to obtain a nano-reinforced tube; wherein the corrosion inhibitor comprises an inorganic corrosion inhibitor; and the melting point of the corrosion inhibitor is higher than 680°C; Step (2): cleaning the nano-reinforced tubes so that the outer walls of the carbon nanotubes form a clean wall surface; obtaining a carbon nanotube-reinforced material; Wherein, in step (2), cleaning the nano-enhanced tubes comprises the following steps: The nano-enhanced tube is cleaned with a mixed solution of alcohol and water; the cleaning frequency is 3 to 8 times; After cleaning the nano-reinforced tubes, the method further includes drying the reinforced tubes to obtain the carbon nanotube-reinforced material; The process of drying the enhanced tube is as follows: firstly, drying naturally in the air, and then drying in an air atmosphere at 100-200° C. for 0.5-4 hours.

2. The method for preparing the carbon nanotube reinforced material according to claim 1, characterized in that: In step (1), loading the carbon nanotube with a corrosion inhibitor comprises the following steps: The purified carbon nanotubes and the corrosion inhibitor are uniformly mixed in water to form a mixed solution; the mixed solution is subjected to a boiling treatment to make the mixed solution boil, thereby causing the corrosion inhibitor to be loaded in the tube body of the purified carbon nanotubes.

3. The method for preparing the carbon nanotube reinforced material according to claim 2, characterized in that: In the mixed solution, the mass ratio of the corrosion inhibitor to the purified carbon nanotubes is greater than 4:

1.

4. The method for preparing the carbon nanotube reinforced material according to claim 2, characterized in that: The purified carbon nanotubes and the corrosion inhibitor are mixed uniformly in water to form a mixed solution, which comprises the following steps: after the purified carbon nanotubes and the corrosion inhibitor are mixed in water, the solution is stirred under a constant temperature environment.

5. The method for preparing the carbon nanotube reinforced material according to claim 4, characterized in that: The temperature of the constant temperature environment is 30-50°C.

6. The method for preparing the carbon nanotube reinforced material according to claim 5, characterized in that: The constant temperature environment is controlled by an oil bath.

7. The method for preparing the carbon nanotube reinforced material according to claim 4, characterized in that: The stirring comprises the following steps: using magnetic stirring and controlling the rotation speed to be greater than 800 rpm.

8. The method for preparing the carbon nanotube reinforced material according to claim 2, characterized in that: The method for preparing purified carbon nanotubes comprises the following steps: adding carbon nanotubes to a mixed solution of HNO3:H2SO4=1:2-4 and subjecting it to ultrasonic oscillation, and then successively filtering, cleaning and drying the carbon nanotubes to obtain purified carbon nanotubes.

9. The method for preparing the carbon nanotube reinforced material according to claim 8, characterized in that: The ultrasonic oscillation time is 1 to 6 hours.

10. The method for preparing the carbon nanotube reinforced material according to claim 8, characterized in that: During the ultrasonic oscillation process, a constant temperature environment is created, and the temperature of the constant temperature environment is 30-60° C. The constant temperature environment is controlled by a water bath.

11. The method for preparing a carbon nanotube reinforced material according to claim 8, characterized in that: The carbon nanotube cleaning process is to repeatedly rinse with deionized water until the filtrate is neutral.

12. The method for preparing a carbon nanotube reinforced material according to claim 8, characterized in that: The temperature for drying the carbon nanotubes is 40-80° C.; the time for drying the carbon nanotubes is 1-3 hours.

13. The method for preparing the carbon nanotube reinforced material according to claim 2, characterized in that: The boiling treatment comprises the following steps: Step S1: evacuating the container where the mixed solution is located to make the mixed solution boil.

14. The method for preparing a carbon nanotube reinforced material according to claim 13, characterized in that: The step of evacuating the container containing the mixed solution comprises the following steps: evacuating the container using a vacuum pump until the pressure is lower than -0.0950 MPa.

15. The method for preparing a carbon nanotube reinforced material according to claim 13, characterized in that: After the container containing the mixed solution is evacuated, the following steps are also included: Step S2: performing pressure relief treatment on the container where the mixed solution is located; Step S3: Repeat steps S1 to S2.

16. The method for preparing a carbon nanotube reinforced material according to claim 15, characterized in that: In step S2, the pressure relief treatment of the container containing the mixed solution includes: releasing the pressure until the air pressure in the container is equal to the atmospheric pressure.

17. The method for preparing a carbon nanotube reinforced material according to claim 15, characterized in that: In step S3, the number of repetitions is 3 to 30 times.

18. The method for preparing a carbon nanotube reinforced material according to claim 17, characterized in that: During the last repetition, the vacuum is maintained for 0 to 120 minutes before the pressure is released.

19. The method for preparing a carbon nanotube reinforced material according to claim 15, characterized in that: After step (1) and before step (2), the method further includes the following steps: The mixed solution after the treatment in step S3 is filtered to obtain nano-enhanced tube filter residue.

20. The method for preparing a carbon nanotube reinforced material according to claim 19, characterized in that: Filtering the mixed solution after the treatment in step S3 comprises the following steps: filtering the mixed solution with filter paper or filter membrane to obtain nano-reinforced tube filter residue, wherein the filter residue comprises nano-reinforced tubes.

21. The method for preparing a carbon nanotube reinforced material according to claim 20, characterized in that: The water is deionized water; the volume ratio of the deionized water to alcohol is 1-3:

1.

22. A carbon nanotube reinforced material, characterized in that: It comprises carbon nanotubes; the carbon nanotubes are loaded with corrosion inhibitors; the outer walls of the carbon nanotubes are clean walls; and the carbon nanotube reinforced material is obtained by the preparation method described in any one of claims 1 to 21.

23. The carbon nanotube reinforced material according to claim 22, characterized in that: The inorganic corrosion inhibitor includes at least one of molybdate, tungstate, vanadate, etc.; and / or, the carbon nanotubes include single-walled carbon nanotubes or multi-walled carbon nanotubes; And / or, the diameter of the carbon nanotube is less than 50 nm; the length of the carbon nanotube is less than 50 μm; And / or, the mass of the corrosion inhibitor loaded in the carbon nanotube body is greater than 3 times the mass of the carbon nanotube body.

24. A composite material, characterized in that It comprises a carbon nanotube reinforced material and a matrix material, wherein the carbon nanotube reinforced material is the carbon nanotube reinforced material described in any one of claims 22-23; and the matrix material is a metal matrix.

25. The composite material according to claim 24, characterized in that The metal matrix includes any one of aluminum alloy and magnesium alloy.

26. A method for preparing a composite material as claimed in claim 25, characterized in that: The steps include: Step 1: Compounding the carbon nanotube reinforced material with a metal matrix to form a carbon nanotube reinforced metal matrix composite material; In step 1, the nanotube-reinforced material is composited with a metal matrix to form a carbon nanotube-reinforced metal matrix composite material, comprising the following steps: Step H1: mixing nanotube reinforcement material powder and metal powder to form a mixed powder; and subjecting the mixed powder to ball milling to obtain a composite material powder; Step H2: forming the composite material powder into an ingot; Step H3: manufacturing the ingot into a carbon nanotube-reinforced metal matrix composite material.

27. The method for preparing the composite material according to claim 26, characterized in that: In step H2, the process of forming the composite material powder into an ingot comprises the following steps: Densification treatment is performed on the composite material powder to obtain a dense carbon nanotube-reinforced metal-based composite material ingot; And / or, in step H3, manufacturing the billet into a carbon nanotube-reinforced metal matrix composite material comprises the following steps: sequentially performing plastic processing and heat treatment on the billet to obtain a carbon nanotube-reinforced metal matrix composite material; And / or, the size of the metal powder is 10-60 μm; and / or, in step H1, the ball milling treatment is performed under a protective gas environment; And / or, the ball-to-material ratio during the ball milling process is 5-15:1; the rotation speed is 100-400 rpm; and the ball milling time of the ball milling process is 6-48 hours; And / or, the process control agent in the ball milling process is at least one of stearic acid and petroleum ether; And / or, in the mixed powder in step H1, the mass fraction of the nanotube reinforcement material is 2.0-6.0 wt.%.

28. The method for preparing the composite material according to claim 27, characterized in that: The protective gas is argon.

29. The method for preparing the composite material according to claim 27, characterized in that: The densification process includes press forming and high temperature sintering.

30. The method for preparing the composite material according to claim 27, characterized in that: The plastic working includes any one of hot extrusion, hot rolling and hot forging.

31. The method for preparing the composite material according to claim 27, characterized in that: The heat treatment includes at least one of solution treatment and aging heat treatment.

Citation Information

Patent Citations

  • Preparing method of high-toughness carbon nanotube enhanced metal-based composite

    CN106756166A